A Comparative Evaluation of Heavy Metals in Commercial Wheat Flours Sold in Calabar-Nigeria - A., Edem Christopher; Iniama, Grace; Osabor, Vincent; Etiuma, Rebbeca; Ochelebe, Matilda (Pakistan Journal of Nutrition, 2009)
The concentrations of heavy metals in commercial brands of wheat flours sold in Calabar-Nigeria were evaluated using Flame Atomic Absorption Spectrophotometer. The result of the analysis table showed the concentrations of the Heavy metals to be Cd (0.002 mg/kg) Cr (0.012 mg/kg) Cu (0.016 mg/kg) Fe (0.040 mg/kg) Ni (0.006.and Zn (0.019 mg/kg) for Dangote flour samples and Cd (0.0004 mg/kg) Cr (0.006 mg/kg) Cu (0.034 mg/kg) Fe (0.020 mg/kg) Ni (0.060 mg/kg) for Golden penny flour sample. Mn, Pb, As and Hg were not detected in all the samples while Zn was only detected in Dangote flour. The results revealed the heavy metals concentrations to follow the trend Fe > Zn > Cu > Cr > Ni > Cd for Dangote flour and Ni > Cu > Fe > Cr > Cd for Golden Penny flour. Keywords Heavy Metals. Golden Penny, Dangote Wheat flour.